Early Population Dynamics of “Candidatus Liberibacter asiaticus” in Susceptible and Resistant Genotypes After Inoculation With Infected Diaphorina citri Feeding on Young Shoots - Alves, Mônica Neli; Cifuentes-Arenas, Juan Camilo; Raiol-Junior, Laudecir Lemos; Ferro, Jesus Aparecido; Peña, Leandro (Frontiers in Microbiology, 2021)
Huanglongbing is a highly destructive citrus disease associated with ‘Candidatus Liberibacter asiaticus’ (Las), a phloem‐limited and non-culturable bacterium, naturally transmitted by the psyllid Diaphorina citri. Although diverse approaches have been used to understand the molecular mechanisms involved in the pathogen-host interaction, such approaches have focused on already infected and/or symptomatic plants, missing early events in the initial days post-inoculation. This study aimed to identify the time-course of Las multiplication and whole-plant colonization immediately following psyllid inoculation. Thus, the experimental approach was to track Las titers after psyllid inoculation in new shoots (NS) of Citrus × sinensis (susceptible), Murraya paniculata (partially resistant), and Bergera koenigii (fully resistant). Soon after psyllid removal, Las titers dropped until the 10-12th day in all three species. Following this, Las titers increased exponentially only in C. x sinensis and M. paniculata, indicating active bacterial multiplication. In C. × sinensis, the Las reached a stationary phase at ~5 log Las cells/g of tissue from the 40th day onwards, while in M. paniculata, Las increased at a lower rate of up to ~3 log Las cells/g of tissue between the 40–60th day, decreasing gradually thereafter and becoming undetectable from the 160th day onwards. In B. koenigii, Las titers decreased from the start and remained undetectable. In C. × sinensis, an average of 2.6 log of Las cells/g of tissue was necessary for Las to move out of 50% of the NS in 23.6 days and to colonize the rest of the plant, causing a successful infection. Conversely, the probability of Las moving out of the NS remained below 50% in M. paniculata and zero in B. koenigii. To our knowledge, this is the first study on Las dynamics and whole-plant colonization during the earliest stages of infection. Identification of critical time-points for either successful multiplication or Las resistance may help to elucidate initial events of Las-host interactions that may be missed due to longer sampling intervals and at later stages of infection.